Measurement report: Wintertime aerosol characterization at an urban traffic site in Helsinki, Finland - K. Teinilä; S. Saarikoski; H. Lintusaari; T. Lepistö; P. Marjanen; M. Aurela; H. Hellén; T. Tykkä; M. Lampimäki; J. Lampilahti; L. Barreira; T. Mäkelä; et al. (Atmospheric Chemistry and Physics)
Physical and chemical properties of particulate matter and concentrations of trace gases were measured at an urban site in Helsinki, Finland, for 5 weeks to investigate the effect of wintertime conditions on pollutants. The measurement took place in a street canyon (traffic supersite) in January–February 2022. In addition, measurements were conducted in an urban background station (UB supersite, SMEAR III, located approx. 0.9 km from the traffic supersite).